Arus Audit Komunikasi Organisasi Dalam Meningkatkan Kualitas Pelayanan Kesehatan Bagi Masyarakat Di Puskesmas Kadungora - Sarah Febriana; Sarah Nabilah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2026)
ABSTRACT Organizational communication plays an important role in supporting the effectiveness of healthcare services through coordination, information sharing, and decision-making. Communication audits are conducted to evaluate the effectiveness of communication systems and identify areas for improvement. This study aims to analyze the role of organizational communication audits in improving the quality of healthcare services at Kadungora Community Health Center. The study employed a descriptive qualitative approach using the organizational communication audit method. Data were collected through observation, in-depth interviews, and documentation involving the head of the health center, healthcare workers, and administrative staff. The findings indicate that organizational communication has been effectively implemented through morning briefings, coordination meetings, monthly mini workshops, and digital communication media. Vertical, horizontal, and cross-sector communication supported work coordination, while two-way communication and feedback mechanisms enhanced information transparency. However, greater clarity in information delivery through several communication media is still needed. Overall, communication audits contribute to improving the quality of healthcare services provided to the community. Keywords: Communication Audit; Organizational Communication; Health Services; Public Health Center; Service Quality. ABSTRAK Komunikasi organisasi berperan penting dalam mendukung efektivitas pelayanan kesehatan melalui koordinasi, penyampaian informasi, dan pengambilan keputusan. Audit komunikasi diperlukan untuk mengevaluasi efektivitas sistem komunikasi serta mengidentifikasi aspek yang perlu diperbaiki. Penelitian ini bertujuan menganalisis audit komunikasi organisasi dalam meningkatkan kualitas pelayanan kesehatan di Puskesmas Kadungora. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode audit komunikasi organisasi. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi terhadap kepala puskesmas, tenaga kesehatan, serta staf administrasi. Hasil penelitian menunjukkan bahwa komunikasi organisasi telah berjalan efektif melalui apel pagi, rapat koordinasi, lokakarya mini bulanan, dan media digital. Arus komunikasi vertikal, horizontal, dan lintas sektor mendukung koordinasi kerja, sedangkan komunikasi dua arah dan mekanisme umpan balik meningkatkan keterbukaan informasi. Meskipun demikian, kejelasan penyampaian informasi pada beberapa media masih perlu ditingkatkan. Audit komunikasi terbukti berkontribusi dalam mendukung peningkatan kualitas pelayanan kesehatan kepada masyarakat. Kata Kunci: Audit Komunikasi; Komunikasi Organisasi; Pelayanan Kesehatan; Puskesmas; Kualitas Pelayanan.